Splenic Autotransplantation after Blunt Spleen Injury in Children - Hojun Lee; Byung Hee Kang; Junsik Kwon; John Cook-Jong Lee (Journal of Trauma and Injury)
Non-operative management has been preferred in blunt spleen injury. Moreover children are more susceptible to post-splenectomy infection, spleen should be preserved if possible. However, splenectomy is inevitable to patients with severe splenic injury. Therefore splenic autotransplantation could be the last chance for preserving splenic function in these patients although efficacy has not proven. Here we reported four cases of children who were underwent splenic autotransplantation successfully after blunt trauma.